Evaluasi Fasilitas Penyimpanan Sementara Limbah Bahan Berbahaya dan Beracun (B3) pada Industri Akumulator Listrik di Kecamatan Taman, Kabupaten Sidoarjo - Naurah Thifal Safitri; Pranandito Wisnu Prabowo; Tuhu Agung Rachmanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Companies operating in the electricity accumulator industry sector, in the production process produce waste in the form of hazardous and toxic materials (B3). The management of B3 waste is carried out based on the provisions stated in the Regulation of the Minister of Environment and Forestry Number 6 of 2021 concerning Procedures and Requirements for Hazardous and Toxic Waste Management. Therefore, the waste generated requires special handling to prevent environmental pollution. Therefore, the waste generated requires special handling so as not to pollute the environment. Hazardous waste management in the electricity accumulator industry includes various stages, both for waste in the solid and liquid phases, namely identification, inventory, packaging, labeling and symbolization, storage, and transportation carried out by third parties. This research aims to assess the current condition of hazardous waste management in the electricity accumulator industry, evaluate it, and provide recommendations that are in line with applicable regulations. The research method used is a descriptive approach. In the inventory process, the electricity accumulator industry requires Temporary Storage Sites (TPS) to store B3 waste before transportation by third parties.